The simplified expression are as follows;
6mn³ - mn² + 3mn³ + 15mn² = 9mn³ + 14mn²
a⁴b³ + 8a⁴b³ = 9a⁴b³
<h3>How to simplify an expression?</h3>
A simplified expression is express to its lowest term.
Therefore,
6mn³ - mn² + 3mn³ + 15mn²
combine like terms
6mn³ + 3mn³ - mn² + 15mn²
9mn³ + 14mn²
a⁴b³ + 8a⁴b³ = 9a⁴b³
learn more on simplification here: brainly.com/question/403991
#SPJ1
Answer:
0
Step-by-step explanation:
-4 times -6x is 24x and-4 x -3 = 12
isolating 24x on the right side we subtract twelve on the right and on the left to get 24x=0 and 24 divided by zero is 0
Answer:
2(n - 6) >= 22
Step-by-step explanation:
2n - 12 >= 22
2n >= 22+12
2n >= 34
n >= 34/2
n >= 17
Answer:
wergeyhrfed
Step-by-step explanation: